Combination Therapy with Secretome of Reovirus-Infected Mesenchymal Stem Cells and Metformin Improves Anticancer Effects of Irinotecan on Colorectal Cancer Cells in vitro - Elhamipour, Maliheh; Soleimanjahi, Hoorieh; Abdoli, Asghar; Sharifi, Negar; Karimi, Hesam; Soleyman Jahi, Saeed; Kvistad, Ruth (Intervirology, 2025)
Introduction: Irinotecan, a topoismorase 1 inhibitor, has been used for the treatment of colorectal cancer. It was shown that monotherapy alone is largely ineffective. The combination therapy was used for antitumor activity. The synergistic anticancer effects of oncolytic reovirus-infected secretome in combination with irinotecan and metformin are evaluated in vitro. The aim of research was to assess anticancer impacts of ReoT3D, irinotecan, metformin in combination, against murine colorectal cancer cells (CT26). Methods: The L929 and the CT26 colorectal cancerous cell lines were treated in vitro with irinotecan, metformin, the Dearing strain of reovirus serotype 3 (ReoT3D) (V), and the secretome of intact (S) or reovirus-infected murine adipose-derived mesenchymal stem cells (SV). The cell viability was measured by MTT, and the apoptosis rate was analyzed by annexin V-FITC staining and flow cytometry 48 and 72 h after treatment. Results: We found that cells exposed to a combination of SV+Met+I had significantly lower cell viability and higher apoptosis rates as compared to cells exposed to Met+I, 48 and 72 h. These results suggest that metformin in combination with irinotecan and reovirus produces a synergistic effect on cell death, and adding reovirus-infected secretome (SV) to a Met+I regimen induces a higher apoptosis rate compared to Met+I alone. Based on the results, the combination of SV+Met+I has induced more apoptosis than S, SV, SV+I, and SV+Met. Also, all of the combined treatments induced apoptosis significantly versus secretome alone. Discussion: In this in vitro study, we found that the combination of T3D reovirus (oncolytic virus) and metformin with the anticancer drug irinotecan resulted in higher rates of growth inhibition and apoptosis induction in the colorectal cancer cell line. This synergistic effect was even more pronounced when using the combination of secretome derived from reovirus-infected AD-MSCs, metformin, and irinotecan. Conclusion: We highlight that the combination of ReoT3D-derived secretome with irinotecan and metformin showed a synergistic anticancer effect on the CT26 cell line, and this strategy may be considered as a new approach against colorectal cancer in the in vitro and in vivo in future studies.